Desarrollo costero y ambientes marino-costeros en Bahía Culebra, Guanacaste, Costa Rica - Sánchez-Noguera, Celeste (2018)
Abstract: Coastal development and marine ecosystems in Culebra Bay, Guanacaste, Costa Rica. Culebra Bay (North Pacific, Costa Rica) is under an accelerated process of coastal development since the implementation of the large-scale tourism development Gulf of Papagayo Project. This study aims to identify changes in the health status of marine ecosystems within the bay, during a 18yr time period (1993-2011). The high sanitary and aesthetic quality of this bay has remained constant through time. However, coral reefs are degraded and dead coral accounts for more than 65 % of benthic coverage, likely due to a combination of natural and anthropogenic factors. During the study period, only one of the developers consortium has proved their commitment to accomplishing the goals of sustainable development, as established in the bay’s Master Plan, through the practice of social and environmental programs. Management of natural resources in Culebra Bay requires the implementation of specific actions to promote the ecosystems’ recovery, with inclusion of all stakeholders. It must consider the current use of natural resources and include water waste management and environmental education programs. Rev. Biol. Trop. 66(Suppl. 1): S309-S327. Epub 2018 April 01.